Reclamation Of A Limestone Quarry To A Natural Plant Community ... - Cohen-Fernández, Anayansi C. (University of Alberta Library, 2012)
Reclamation of thousands of limestone quarries around the world is challenged by an extremely limiting environment, including steep slopes, high calcium carbonate substrates with low nutrients and low water holding capacity. These issues were addressed at the Exshaw quarry in the Rocky Mountains of southern Alberta. Reintroduction of key components, such as vegetation and ameliorated soil were expected to speed recovery of ecosystem functioning processes. Erosion control blankets and combinations of fertilizer, sulfur and organic amendments at different application rates were evaluated in three limestone substrates in the greenhouse and field. Amendments were hay, straw, wood shavings, pulp mill biosolids, beef manure compost, beef manure mix (6:1:1 manure, waste feed, wood chips), topsoil and clean fill. Revegetation with seeded native grasses (Poa alpina, Agropyron trachycaulum, Elymus innovatus, Festuca saximontana, Trisetum spicatum), transplanted and seeded woody species (Picea glauca, Pseudotsuga ...